Fetal Sex and Fetal Environment Interact to Alter Diameter, Myogenic Tone, and Contractile Response to Thromboxane Analog in Rat Umbilical Cord Vessels - Sicotte, Benoit; Brochu, Michèle (Frontiers in Physiology, 2021)
Fetal growth needs adequate blood perfusion from both sides of the placenta, on the maternal side through the uterine vessels and on the fetal side through the umbilical cord. In a model of intrauterine growth restriction (IUGR) induced by reduced blood volume expansion, uterine artery remodeling was blunted. The aim of this study is to determine if IUGR and fetus sex alter the functional and mechanical parameters of umbilical cord blood vessels. Pregnant rats were given a low sodium (IUGR) or a control diet for the last 7 days of pregnancy. Umbilical arteries and veins from term (22day) fetal rats were isolated and set-up in wire myographs. Myogenic tone, diameter, length tension curve and contractile response to thromboxane analog U46619 and serotonin (5-HT) were measured. In arteries from IUGR fetuses, myogenic tone was increased in both sexes while diameter was significantly greater only in male fetuses. In umbilical arteries collected from the control group, the maximal contraction to U46619 was lower in females than males. Compared to the control groups, the maximal response decreased in IUGR male arteries and increased in female ones, thus abolishing the sexual dimorphism observed in the control groups. Reduced contractile response to U46619 was observed in the IUGR vein of both sexes. No difference between groups was observed in response to 5HT in arteries. In conclusion, the change in parameters of the umbilical cord blood vessels in response to a mild insult seems to show adaptation that favors better exchange of deoxygenated and wasted blood from the fetus to the placenta with increased myogenic tone.